Safety Zone Facility Needs Study School (Zoss) on Dewi Sartika Street (Case Study: State Middle School 6 and State Senior High School 3 Palu) - Madani, Medinah Wirda; Bahar, Taslim; Arifin, Syamsul (Publica Scientific Solution, 2025)
Dewi Sartika Street in Palu is home to two major schools SMP Negeri 6 and SMA Negeri 3 which face increasing safety risks due to high vehicle speeds in school zones. To address this, the government proposes the implementation of School Safety Zones (ZoSS), a time-based speed control program designed to minimize traffic accidents by limiting vehicle speed and improving pedestrian safety. This study aims to assess the necessity of ZoSS facilities in the area surrounding the two schools by analyzing pedestrian and escort behavior, vehicle speed, and infrastructure needs. The research method follows the Regulation of the Director General of Land Transportation No: SK.3236/AJ.403/DRJD/2006 and utilizes a normal distribution statistical approach (Z-test) to compare actual field data with national safety standards. The findings reveal that current conditions on Dewi Sartika Street are unsafe for school children, particularly in terms of crossing behavior and vehicle speed. Consequently, the implementation of a School Safety Zone is deemed necessary. The recommended ZoSS design is a 2/2UD-25 configuration with a 2-lane undivided road (2/2-TT), a stopping sight distance of 50–85 meters, a maximum speed of 25 km/h, and a zone length of 150 meters. Essential facilities include school zone markings, zebra crossings, traffic signs, yellow zigzag lines, pedestrian guides, rumble strips, pelican crossing signals, and sidewalks. This study confirms the urgent need for targeted safety infrastructure to reduce accident risk and protect students in urban school areas.